Biomechanics of the Human Urinary Bladder - Miftahof, Roustem N.; Nam, Hong Gil.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
As a research subject, the biomechanics of the urinary bladder are relatively young, yet medical problems associated with them are as old as mankind. Offering an update on recent achievements in the field, the authors highlight the underlying biological, chemical and physical processes of bladder function and present the systematic development of a mathematical model of the organ as a thin, soft biological shell. The book will be a valuable resource for postgraduate students and researchers interested in the applications of computational mathematics and solid mechanics to modern problems in biomedical engineering and medicine.
The Bladder as a Dynamic System -- Investigations into Biomechanics of the Bladder -- Geometry of Thin Shells -- Essentials of the Theory of Soft Shells -- Continual Model of the Detrusor -- A Model of the Detrusor Fasciculus -- The Intrinsic Regulatory Pathways -- The Synaptic Transmission -- Pharmacology of Detrusor Activity -- Human Urinary Bladder as a Soft Biological Shell -- Challenges in Human Urinary Bladder Mechanics.
Keywords: Human physiology; Biomathematics; Systems biology; Bioinformatics; Biophysics; Biological physics; Human Physiology; Physiological, Cellular and Medical Topics; Systems Biology; Computational Biology/Bioinformatics.; Biological and Medical Physics, Biophysics